The Study of Alternative Splicing Events in Human Induced Pluripotent Stem Cells From a Down's Syndrome Patient - Wang, Yunjie; Li, Zexu; Yang, Guanheng; Cai, Linlin; Yang, Fan; Zhang, Yaqiong; Zeng, Yitao; Ma, Qingwen; Zeng, Fanyi (Frontiers in Cell and Developmental Biology, 2021)
Down's syndrome (DS) is one of the most commonly known disorders with multiple congenital disabilities. Besides severe cognitive impairment and intellectual disability, individuals with DS also exhibit additional phenotypes of variable penetrance and severity, with one or more comorbid conditions, including Alzheimer's disease, congenital heart disease, or leukemia. Various vital genes and regulatory networks had been studied to reveal the pathogenesis of the disease. Nevertheless, very few studies have examined alternative splicing. Alternative splicing (AS) is a regulatory mechanism of gene expression when making one multi-exon protein-coding gene produce more than one unique mature mRNA. We employed GeneChip Human Transcriptome Array 2.0 (HTA 2.0) for the global gene analysis with hiPSCs from DS and healthy individuals. Examining differentially expressed genes (DEGs) in these groups and focusing on particularly transcripts with AS, 466 up-regulated and 722 down-regulated genes with AS events were found. These genes were significantly enriched in biological processes, such as cell adhesion, cardiac muscle contraction, and immune response, through gene ontology (GO) analysis of DEGs. Candidate genes such as FN1 were further explored for potential key factors playing in DS. This study could provide important insights into the potential roles AS play in DS.